Clinical Features and C-Reactive Protein as Predictors of Bacterial Exacerbations of COPD - Francis,Nick A; Gillespie,David; Wootton,Mandy; White,Patrick; Bates,Janine; Richards,Jennifer; Melbye,Hasse; Hood,Kerenza; Butler,Christopher C (International Journal of Chronic Obstructive Pulmonary Disease, 2020)
Nick A Francis,1 David Gillespie,2 Mandy Wootton,3 Patrick White,4 Janine Bates,2 Jennifer Richards,3 Hasse Melbye,5 Kerenza Hood,2 Christopher C Butler6 1Primary Care, Population Sciences and Medical Education, University of Southampton, Southampton, England, UK; 2Centre for Trials Research, Cardiff University, Cardiff, Wales, UK; 3Specialist Antimicrobial Chemotherapy Unit, Microbiology Cardiff, Public Health Wales, Cardiff, Wales, UK; 4School of Population Health and Environmental Sciences, King’s College London, London, England, UK; 5Department of Community Medicine, UIT the Arctic University of Norway, Tromsø, Norway; 6Nuffield Department of Primary Care Health Sciences, University of Oxford, Oxford, England, UKCorrespondence: Nick A FrancisPrimary Care, Population Sciences and Medical Education, University of Southampton, Aldermoor Health Centre, Southampton SO16 5ST, UKEmail nick.francis@soton.ac.ukIntroduction: Identifying predictors of bacterial and viral pathogens in sputum from patients with acute exacerbations of chronic obstructive pulmonary disease (COPD) may help direct management.Methods: We used data from a trial evaluating a C-reactive protein (CRP) point of care guided approach to managing COPD exacerbations in primary care. We used regression analyses to identify baseline clinical features, including CRP value in those randomized to testing, associated with bacterial, viral or mixed infections, defined by the presence of bacterial and viral pathogens in sputum, detected by culture or polymerase chain reaction (PCR), respectively.Results: Of 386 participants with baseline sputum samples, 79 (20.5%), 123 (31.9%), and 91 (23.6%) had bacterial, viral/atypical, and mixed bacterial/viral/atypical pathogens identified, respectively. Increasing sputum purulence assessed by color chart was associated with increased odds of finding bacterial and mixed (bacterial and viral/atypical) pathogens in sputum (area under the ROC curve (AUROC) for bacterial pathogens =0.739 (95% CI: 0.670, 0.808)). Elevated CRP ...